ANALISIS KEBIJAKAN PENDIDIKAN ISLAM DAN IMPLIKASINYA BAGI MADRASAH DULU-SEKARANG(SKB 3 Menteri Tahun 1975, UUSPN No. 2 Tahun 1989 dan UU. No. 16 Tahun 2001) - Sayid Ahmad Ramadhan; Zainap Hartati (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The development of madrasah as part of Islamic nuasa educational institutions in Indonesia from the past until now has shown its existence even though it has received less attention from the government. Nevertheless, the extra struggle is always echoed by education observers through the Ministry of Religion and the Ministry of Education and Culture and the Ministry of Home Affairs wanting to fulfill their rights as a forum for intelligence for the community and a form of support from the government because the purpose of the upbringing carried out is in accordance with the objectives of national education. This study describes and then analyzes the implications of the policies contained in the SKB 3 Menteri Tahun 1975, UUSPN No. 2 Tahun 1989, and UU No. 16 Tahun 2001 on Islamic nuance educational institutions. Library research is used as a research method to look at related sources, namely articles (scientific papers), books and so on. The results showed that the changes felt by educational institutions with Islamic nuances to these policies include: 1. The inclusion of madrasas on the national education mechanism, 2. Existence Is Recognized and Output Has Freedom, Guaranteed Financing from the Government, 4. Equitable Application of Curriculum, 5. Wages or Salaries of Teachers Paid by the Government, dan 6. Received Legal Protection from the Government. On the other hand, the government needs and is obliged to conduct an evaluation (assessment) regarding the realization and reality in the field of policies aimed at improving and improving existing performance. So as to create justice for each educational institution in Indonesia, especially with Islamic nuances.